2023
DOI: 10.3389/fimmu.2022.1074762
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative corticosteroid treatment impairs tumor-infiltrating dendritic cells in patients with newly diagnosed adult-type diffuse gliomas

Abstract: IntroductionAdult-type diffuse gliomas are malignant primary brain tumors characterized by very poor prognosis. Dendritic cells (DCs) are key in priming antitumor effector functions in cancer, but their role in gliomas remains poorly understood.MethodsIn this study, we characterized tumor-infiltrating DCs (TIDCs) in adult patients with newly diagnosed diffuse gliomas by using multi-parametric flow cytometry and single-cell RNA sequencing.ResultsWe demonstrated that different subsets of DCs are present in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…In addition to corticosteroid-dependent reduction of MHCII and CD40 on DC, they also identified a heterogeneous population of DC within patient HGG samples, including cDC1, cDC2, and moDC. cDC1 comprised the smallest portion, and significant levels of pDC were only detected in one out of a total of five untreated patients [46]. In a single cell RNA-sequencing study, Antunes et al confirmed the reported DC heterogeneity in humans and extended these findings in a murine model of GBM.…”
Section: Dendritic Cell Infiltration Of Hgg: Who Are the Players And ...mentioning
confidence: 82%
“…In addition to corticosteroid-dependent reduction of MHCII and CD40 on DC, they also identified a heterogeneous population of DC within patient HGG samples, including cDC1, cDC2, and moDC. cDC1 comprised the smallest portion, and significant levels of pDC were only detected in one out of a total of five untreated patients [46]. In a single cell RNA-sequencing study, Antunes et al confirmed the reported DC heterogeneity in humans and extended these findings in a murine model of GBM.…”
Section: Dendritic Cell Infiltration Of Hgg: Who Are the Players And ...mentioning
confidence: 82%
“…However, considering that antigen presentation occurs at this CNS immune interface during neuroinflammation [39], we speculate meninges may also harbor the CI cycle 1 3 anti-tumoral T-cell activation and a weaker immunological response in GBM [20]. Notably, although DCs are negligible in healthy brain parenchyma [21], almost all subsets of DCs can be observed in the core lesions of gliomas [22]. Thus, released tumor antigens can also captured by DCs infiltrated in GBM [23].…”
Section: A Unique CI Cycle In Gbmmentioning
confidence: 95%
“…However, other research groups found no significant difference in neutrophil counts in patients receiving or not receiving steroid therapy ( 108 ) or revealed only a weak correlation between the dexamethasone dose and NLR ( 109 ). Finally, perioperative corticosteroid treatment impaired tumor-infiltrating dendritic cells in patients with newly diagnosed gliomas ( 110 ). Altogether, in accordance with in vitro and ex vivo studies, dexamethasone (without radiochemotherapy) adversely affects the immune system of patients with cancer.…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 99%